2017
DOI: 10.1037/apl0000109
|View full text |Cite
|
Sign up to set email alerts
|

Stress and well-being at work: A century of empirical trends reflecting theoretical and societal influences.

Abstract: In various forms, research on stress and well-being has been a part of the () since its inception. In this review, we examine the history of stress research in by tracking word frequencies from 606 abstracts of published articles in the journal. From these abstracts, we define 3 eras: a 50 year-era from 1917 to 1966, a 30-year era from 1967 to 1996, and a 20-year era from 1997 to the present. Each era is distinct in terms of the number of articles published and the general themes of the topic areas examined. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
289
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(307 citation statements)
references
References 119 publications
(172 reference statements)
11
289
1
6
Order By: Relevance
“…However, despite such measures by governments or individual organizations and the recognition in research that ICTs have profoundly changed work and non-work life as well as work-life boundaries (Bliese et al 2017;Colbert et al 2016), the evidence regarding the antecedents and consequences of work-related ICT use during non-work time is less clear. This is partly because there is a lack of conceptual clarity regarding what constitutes work-related ICT use during non-work time and whether such 'hidden work' would actually count as compensable work from a legal perspective (Brecher and Magnus 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite such measures by governments or individual organizations and the recognition in research that ICTs have profoundly changed work and non-work life as well as work-life boundaries (Bliese et al 2017;Colbert et al 2016), the evidence regarding the antecedents and consequences of work-related ICT use during non-work time is less clear. This is partly because there is a lack of conceptual clarity regarding what constitutes work-related ICT use during non-work time and whether such 'hidden work' would actually count as compensable work from a legal perspective (Brecher and Magnus 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mechanisms, we develop theory about the mediators linking helping pressure with instigated incivility and organization‐directed deviance by drawing on the consensus across decades of research that work stressors have affective and cognitive effects (Bliese, Edwards, & Sonnentag, ). This literature, as well as extant research positioning deviance as arising from both affective (Judge, Scott, & Ilies, ) and cognitive (Lin, Ma, & Johnson, ) processes, gives us insight into two mechanisms—negative affect and cognitive depletion—that may explain why helping pressure leads to deviant acts.…”
Section: Introductionmentioning
confidence: 99%
“…These wellness programs appear to be enjoying a prolific period of growth, and typically focus on the person-orientated methods to enable employees to better resist stress (i.e., resilience; Hegney et al, in press). It is noticeable that despite scholarly calls for improved stress interventions (e.g., Bliese et al, 2017;Brough & Biggs, 2015a), and recognition of the increasing costs of occupational stress (Hassard et al, 2018), it remains relatively rare for organisations to undertake systematic job-orientated stress interventions, despite these being recognised as the best opportunity to actually reduce stress experiences for workers (Biggs et al, 2014a;Murphy, 1988). In comparison, the lower cost of organisational wellness programs certainly has corporate appeal.…”
Section: Work Stress Management Scalementioning
confidence: 99%
“…A recent review described occupational stress as a "sizeable financial burden on society" (Hassard, Teoh, Visockaite, Dewe, & Cox, 2018, p. 1). A second recent review reported that occupational stress journal articles have increased steadily in number since 2002; indicative of the increased interest and developments within this field (Bliese, Edwards, & Sonnentag, 2017). The key demographical, technological, societal, and financial reasons for this steady increase in occupational stress experiences by a wide range of workers have been reported (e.g., Brough, O'Driscoll, Kalliath, Cooper, & Poelmans, 2009), while more effective strategies to assist workers to better manage their stress experiences are emerging (e.g., Biggs, Brough, & Barbour, 2014a).…”
Section: Introductionmentioning
confidence: 99%